Efektivitas Model Pembelajaran Simulasi Berbantuan Permainan Geo Explore pada Mata Pelajaran Geografi Siswa Kelas XI IPS 1 SMA Negeri 6Kerinci - Nirwana, Nirwana (Jurnal Ilmiah Dikdaya, 2022)
This research is a classroom action research . Study this aim for study effectiveness of learning model simulation help game Geo Explore from achievement activity study student, result study student, response positive students, and activities study student in learning simulation with results study Geography student class XI IPS 1 Public High School 6 Kerinci. Method research used _ is pre- experiment with design one group pre-test post-test. Population in study this is whole student class XI IPS in public high school 6 Kerinci, which consists of from three class, that is class XI IPS 1, XI IPS 2, and XI IPS 3. Sample taken with technique purposive sampling, namely technique taking with provision certain. Terms is ability study same student seen from UTS value of the eye lesson Geography odd semester year lesson 2021/2022, so that obtained class XI IPS 1. Engineering retrieval of data used is technique documentation, observation, test, and questionnair. Technique data analysis used is analysis descriptive, and t test.Results analysis show level activity study student in category very tall with an average score of 52.62 or 88%. T test two mean, get results t count > t table, Ho is rejected or mark post-test good fromon mark pre-test. Test average score previous 78.21 increase becomes 84.14, happens enhancement by 7.60%. Completeness results study student proved with t test one average, result t count > t table, Ho is rejected so results study finished. Completeness classic achieved with figure of 86.20%. Average score positive student 52.62 or 82.75 %, with category good and level activity study student belong to very active as many as 24 people and 5 people categories active. Based on results study concluded that the learning model simulation help game Geo Explore effective and could Upgrade results study students